Website-Based Marketing Information System for UMKM Products at Asaul Store Using the ADDIE Method - Zamorano, Ifan; Indahyanti, Uce (Research Parks Publishers, 2025)
UMKM (Usaha Mikro, Kecil, dan Menengah) play a significant role in the economy but often face challenges in marketing their products broadly. Marketing is a crucial aspect in the development of UMKM, especially in today's digital era. However, many UMKM still encounter obstacles in reaching a wider market due to limitations in traditional marketing methods. Toko A’saul, an UMKM business, uses a website-based information system for marketing its products, which effectively enhances its marketing reach and product competitiveness. Website-based marketing positively impacts the increase in sales and market reach of UMKM. Additionally, this system enables UMKM to better compete with larger businesses in the digital market. Through the implementation of a website-based marketing platform, UMKM are expected to maximize their potential in attracting new customers, expanding market share, and improving overall business performance. Moreover, this platform enhances customer satisfaction by offering a better shopping experience and more responsive services.